2007
DOI: 10.1093/aje/kwm203
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Conditions and Brain Tumor Risk

Abstract: An inverse association between allergic conditions and glioma risk has been reported previously. In this large population-based case-control study, the authors identified cases diagnosed with glioma or meningioma in Denmark, Norway, Finland, Sweden, and southeast England between 2000 and 2004. Detailed information on self-reported physician-diagnosed allergic conditions was collected from 1,527 glioma cases, 1,210 meningioma cases, and 3,309 randomly selected controls. Logistic regression showed an odds ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
135
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 31 publications
14
135
4
Order By: Relevance
“…Our results support those from case-control studies based on self-reported allergic diseases (5-7, 16, 17, 28-32) and especially those of one case-control study using IgE measurement at the time of tumour diagnosis (19). In two case-control studies, associations between age at onset or duration of allergies (in years) and glioma risk were investigated using questionnaire data, but with conflicting results (16,18). In one cohort study (10), a reanalysis of data from individuals who reported allergies 5 years before a diagnosis of brain tumours were similar to results of the whole cohort.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results support those from case-control studies based on self-reported allergic diseases (5-7, 16, 17, 28-32) and especially those of one case-control study using IgE measurement at the time of tumour diagnosis (19). In two case-control studies, associations between age at onset or duration of allergies (in years) and glioma risk were investigated using questionnaire data, but with conflicting results (16,18). In one cohort study (10), a reanalysis of data from individuals who reported allergies 5 years before a diagnosis of brain tumours were similar to results of the whole cohort.…”
Section: Discussionsupporting
confidence: 78%
“…Most studies of allergies and brain tumours used questionnaire data; hence, allergies were self-reported (5,7,(16)(17)(18) and could therefore be influenced by recall biases or differential misclassification. Only one case-control and one cohort study defined the atopic status of the study participants by measuring total serum IgE levels in glioma cases and controls in addition to the questionnaire data (10,19) and another cohort study used a skin prick test (12).…”
mentioning
confidence: 99%
“…A recent report in a United Kingdom population showed a slight but nonsignificant reduction in risk associated with ever use of antihistamines by those reporting hay fever, allergic rhinitis, or conjunctivitis (7). A related report from the Nordic-United Kingdom pooled study also found a nonsignificant 22% reduction in the risk of ever antihistamine use in those reporting hay fever (10). These reports could differ from the current findings because of the definition of long-term antihistamine use in the current study or because of differences in use of these drugs between the different study populations.…”
Section: Discussionmentioning
confidence: 97%
“…These drugs act to alleviate symptoms associated with histamine release after exposure to allergens. We speculated that antihistamine use would be more common among persons prone to allergy and more likely to be associated with a decrease in risk, as has been report in previous studies (6,7,10). We used data from a case-control study on adult glioma in greater Houston, TX, to examine the relationships between these medications and glioma risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation